Hubungan Antara Dukungan Sosial, Motivasi Berprestasi dan Keterlibatan Siswa Di Sekolah - Nur Saqinah (El-Idare, 2017)
Lackof students’ engagement at school has become renewed issue both nationally and globally. Family, friends and teachers are associated with the students’ engagement at school. However, achievement motivation is a part of psychological factor contributing toward students’ engagement. This study aimedto examine the relationship of social support, achievement motivation and students’ engagement. Participants were  276 students of senior high school Sumberpucung Malang. Proportional sampling were used to determine the participants of this study. Data were analyzed with multiple regression analysis. The results showed that there was a significant relationship between social support, achievement motivation and students’ engagement.